2017
DOI: 10.1371/journal.pone.0179445
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ki67 re-assessment at time of disease progression in patients with pancreatic neuroendocrine neoplasms

Abstract: BackgroundAlthough re-assessment of proliferative activity by K67 evaluation during the course of neuroendocrine neoplasms (NENs) is recommended in selected patients, its impact on patients’ management is not clear due to the lack of data supporting this practice.AimTo investigate Ki67 change at time of progressive disease (PD) in entero-pancreatic NENs (EP-NENs).Patients and methodsRetrospective analysis of sporadic EP-NENs which received histological re-assessment after PD once radiologically documented.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 15 publications
5
47
3
Order By: Relevance
“…PanNET. This proportion of high-grade progression was larger than that reported by Panzuto et al [14], where 4 (17%) out of 24 cases progressed to a high-grade PanNET. Smaller case series also described high proportions of patients having evolution of their, underscoring that the disease course of PanNET is incompletely understood [10].…”
Section: Discussioncontrasting
confidence: 62%
“…PanNET. This proportion of high-grade progression was larger than that reported by Panzuto et al [14], where 4 (17%) out of 24 cases progressed to a high-grade PanNET. Smaller case series also described high proportions of patients having evolution of their, underscoring that the disease course of PanNET is incompletely understood [10].…”
Section: Discussioncontrasting
confidence: 62%
“…Our previous study indicated that S100A12 expression was correlated with the depth of invasion, and it was evaluated as an independent risk factor for poor overall survival of GC [22]. p53 and Ki67 are established markers for cancer progression [27,28]. In the current study, we found that there was no correlation between expression of TM4SF1 and USP10, S100A12, p53, or Ki67 expression in GC, suggesting that TM4SF1 plays a distinct role in GC invasion and metastasis from those of USP10, S100A12, p53, or Ki67, although they all contribute to cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is upregulated in dividing cells and involved in ribosomal RNA transcription. Since the initial description of Ki-67 in PAs by Burger et al (1986), multiple researchers have attempted to correlate its value with clinicopathological parameters and its predictive and prognostic value (Salehi et al 2009, Heaney 2011, 2014, Zaidi et al 2016, Raverot et al 2018a, much as has been achieved with NETs (Kloppel 2017, Panzuto et al 2017. Thapar et al reviewed the Ki-67 index in 77 PAs and carcinomas and suggested that the cut-off value of 3% distinguishes invasive from non-invasive adenomas with 97% specificity and 73% sensitivity (Thapar et al 1996a); this cut-off was therefore adopted in the previous WHO criteria in 2004.…”
Section: Tumour Proliferationmentioning
confidence: 99%